Effect of Sorghum Flour Addition on In Vitro Starch Digestibility, Cooking Quality, and Consumer Acceptability of Durum Wheat Pasta - Khan, I.; Yousif, A.; Johnson, Stuart; Gamlath, S. (Wiley-Blackwell Publishing, Inc., 2014)
Whole grain sorghum is a valuable source of resistant starch and polyphenolic antioxidants and its addition into staple food like pasta may reduce the starch digestibility. However, incorporating non durum wheat materials into pasta provides a challenge in terms of maintaining cooking quality and consumer acceptability. Pasta was prepared from 100% durum wheat semolina (DWS) as control or by replacing DWS with either wholegrain red sorghum flour (RSF) or white sorghum flour (WSF) each at 20%, 30%, and 40% incorporation levels, following a laboratory scale procedure. Pasta samples were evaluated for proximate composition, in vitro starch digestibility, cooking quality, and consumer acceptability. The addition of both RSF and WSF lowered the extent of in vitro starch digestion at all substitution levels compared to the control pasta. The rapidly digestible starch was lowered in all the sorghum-containing pastas compared to the control pasta. Neither RSF or WSF addition affected the pasta quality attributes (water absorption, swelling index, dry matter, adhesiveness, cohesiveness, and springiness), except color and hardness which were negatively affected. Consumer sensory results indicated that pasta samples containing 20% and 30% RSF or WSF had acceptable palatability based on meeting one or both of the preset acceptability criteria. It is concluded that the addition of wholegrain sorghum flour to pasta at 30% incorporation level is possible to reduce starch digestibility, while maintaining adequate cooking quality and consumer acceptability.